Construction, Validity, and Reliability of the Pedagogical Competence Assessment Instrument for Proficient Teachers - Jusuf Blegur; Andreas J. F. Lumba; Berliana; Intan Christine Adriani Siki; Harmawati; Alfred Tobok Siahaan; Haira; Vena Yuliana (Ital Publication, 2026)
This study aims to develop and evaluate the Pedagogical Competence Assessment for Proficient Teachers (PCAI-PT) as an instrument for assessing teachers’ pedagogical competence in Indonesia. The research employed a development method based on the ADDIE framework (Analyze, Design, Develop, Implement, and Evaluate). Thirteen pedagogical competence items representing core skills of novice expert teachers were formulated from document analysis. These items were validated by six expert raters and tested on 231 teachers across various educational levels. Validation results indicated that all PCAI-PT items were valid after revision, with Aiken’s V ranging from 0.78 to 1.00. Intraclass correlation analysis showed increased inter-rater consistency from the initial validation to revalidation, demonstrating strong inter-rater reliability. Construct testing using CFA revealed that all items met the criteria, with factor loadings >0.70, Cronbach’s alpha and composite reliability >0.70, and AVE >0.50. Discriminant validity was confirmed, and model fit indices indicated good to excellent fit (RMSEA = 0.088; SRMR = 0.034; CFI = 0.955). Concurrent validity testing using the Kruskal-Wallis test showed no significant differences across educational levels (p>0.05), indicating consistent application of the instrument. Overall, PCAI-PT is valid, reliable, and representative, providing a comprehensive and sustainable tool for assessing teachers’ pedagogical competence across diverse educational contexts.